Canvas LMS Course Design - Second Edition - John, Ryan (Packt Publishing, 2021)
A simple, easy-to-follow guide to learning the advanced features and integrated services of Canvas for creating a transformative and personalized educational experience Key Features Simplify online and hybrid learning with Canvas with the help of this updated second edition Discover best practices to engage with students as they complete assignments and receive feedback through the Gradebook Follow clear directions to use Canvas tools and features for your educational requirements Book Description Canvas is an online learning management system (LMS) and one of the most powerful teaching tools that educational institutions worldwide have adopted thanks to its streamlined functionality, intuitive user interface, and robust features. This revised second edition of Canvas LMS Course Design will show you how to design, create, and teach engaging classes in online, hybrid, or fusion settings using the Canvas LMS. The book will guide you through the steps of setting up your Canvas account, creating activities and assignments, designing and customizing the course layout, and teaching your course. Whether you're using an institutional or Free-for-Teacher account, you'll be able to use Canvas for grading, feedback, and communication with and between students. As you progress, you'll learn how to integrate external apps and services with Canvas. Finally, the book features an exclusive section detailing how you can use Canvas' built-in resources as well as other resources to tackle challenges while working with the LMS. Throughout, this book will give you the technical knowledge you need to create unique learning experiences for students. By the end of this Canvas LMS Course Design, you'll be able to successfully teach online with the help of logical descriptions and step-by-step screenshots that clearly explain how to build a phenomenal course. What you will learn Understand online learning as a powerful and unique tool for student growth Create, access, and personalize your user account and profile settings in Canvas Generate, upload, and import course content for students to engage with as participants in your courses Design and sequence the content of your course to present information and activities with clarity and simplicity Discover expert techniques for designing a curriculum and creating activities Explore Canvas features that meet your educational needs, such as online assessments and content delivery Who this book is for This book is for educa...